METABOLIC SYNDROME AND ITS PREVENTION IN UZBEKISTAN - Hiloloy Ruzmatova Kabilovna (International Journal of Innovations in Engineering Research and Technology, 2023)
This article aims to study the occurrence of metabolic syndrome in Uzbekistan, analyze relevant literature and propose preventive measures. The study uses a multifaceted approach combining epidemiological data, lifestyle analysis and health strategy. The findings shed light on the current scenario and emphasized the need to take comprehensive measures to mitigate the impact of metabolic syndrome on the population of Uzbekistan.